The new encyclopedia in 30 volumes. macropedia VOL. 10 / William Benton - Benton, William (1977)
Nature and extent of Jainism, history and background, myhology, doctrines of Jainism, mythology, ritual practices and religious and social institutions, the landscape, the people, history, the national economy, administration and conditions, cultural life and institutions, prospects for the future, the natural environment, the landscape under human settlement, groups historically associated with the contemporary country.